Penerapan ISAK 35 Tentang Laporan Keuangan Organisasi Non-Laba pada Gereja Methodist Indonesia Gideon Bunut - Purba, Sahala; Sihombing, Vivin Caroline; Andy, Stefanus (Politeknik Negeri Bengkalis, 2023)
The thorough documentation and proper disclosure of pertinent accounting policies, estimates, and risks are essential for both preparing and presenting financial statements. Due to its crucial nature for non-profit entities, this carries significant weight for both the Indonesian Methodist Church and analogous organizations. The development of the most recent interpretation for financial reporting standards, namely ISAK 35, directly stems from the revisions in PSAK 1. With the implementation of this standard, GMI Gideon Bunut will find it more convenient to streamline processes and facilitate the aggregation of external resources. This study was carried out with the objective of comprehending the alignment between the financial statements of GMI Gideon Bunut and those in accordance with ISAK 35. This study employs a qualitative approach along with a descriptive analysis, juxtaposing the stipulations within ISAK 35 against the implementation delineated in the financial reports of the Gideon Bunut Indonesian Methodist Church. Researchers use vigilant monitoring and observational methods to extract data. The findings uncover a nonconformity between GMI Gideon Bunut's financial report and ISAK 35, as the Indonesian Methodist Church's financial statement solely encompasses records of fund receipts and expenditures. Consequently, this investigation concludes that GMI Gideon Bunut's financial reporting has not progressed in accordance with the standards outlined in ISAK 35.Keywords: ISAK 35, Financial Report, Church